Superior HR for Advanced Indonesia - Afniar, Defa (Westscience Press, 2023)
Studies References this conducted for now: Analysis creation Source power man superior in Indonesia. In this study, the method used is qualitative with a library study approach research ). The results of the research show that: there are two kinds of superior Human Resources, namely 1) individualistic excellence which is considered as a reflection of human greed because his superiority is used for himself and his personal satisfaction, and 2) participatory excellence which develops the principles of fair competition to find ways, process and result best